2018
DOI: 10.3389/fphys.2018.01687
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recreational Ski Mountaineering on Cumulative Muscle Fatigue – A Longitudinal Trial

Abstract: Sport is known to have many positive effects on mental and physical health. High-intensity exercise is considered to decrease muscle strength and induce muscle fatigue, which is associated with a higher risk of injury. In recreational alpine skiers, a decrease of eccentric peak hamstring torque, as an indication of muscle fatigue, occurs even after 1 day of skiing. The popularity of ski mountaineering is increasing enormously, but no studies are available on its effects on muscle strength. Therefore, the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…Despite the reported decrease in quadriceps and hamstrings muscle strength after recreational ski mountaineering in healthy participants [16], we found no indication of muscle fatigue, expressed by strength loss in the operated leg. Neither a single day of ski mountaineering nor a complete week of repeated ski tours led to a decrease in muscle strength.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Despite the reported decrease in quadriceps and hamstrings muscle strength after recreational ski mountaineering in healthy participants [16], we found no indication of muscle fatigue, expressed by strength loss in the operated leg. Neither a single day of ski mountaineering nor a complete week of repeated ski tours led to a decrease in muscle strength.…”
Section: Discussioncontrasting
confidence: 97%
“…Therefore, similar to alpine skiing, ski mountaineering has a certain impact on muscle fatigue and has to be considered as high-impact sport for patients with TKA as well. In a recent study on ski mountaineering with healthy subjects, participating in a week of consecutive ski tours, we found that muscle strength was decreased already after the first ski tour and remained at a lower level without any cumulative effect during the time course of the week [16]. Similar to alpine skiing, ski mountaineering can be considered as a high-impact sports activity; however, evidence-based recommendations for patients with a TKA are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Although there was no significant association in the present study, off-piste training might be a preventive measure, as increased muscle strength reduces early muscle fatigue and the concomitant risk of injury. 15 While the difference was not statistically significant, the injury rate in advanced ski tourers (3.0 injuries/1000 h) was higher than in experts (1.1 injuries/1000 h) and beginners (1.8 injuries/1000 h). Previous injury surveillance studies have shown that more experience as such seems to be a preventive measure, as poorer technical skills were associated with injuries.…”
Section: Discussionmentioning
confidence: 77%
“…Although there was no significant association in the present study, off-piste training might be a preventive measure, as increased muscle strength reduces early muscle fatigue and the concomitant risk of injury. 15…”
Section: Discussionmentioning
confidence: 99%
“…There were some limitations in scientific interpretation because the statistical differences were not confirmed in all the sections. However, there were some interesting previous results [ 56 ] that confirmed the maximum torque increase in the quadriceps and hamstrings by applying SMR to cross-country skiers with varying inclinations of the cycling course. The longest significant difference in some sections of the uphill road resulted from improved exercise capacity due to SMR.…”
Section: Discussionmentioning
confidence: 95%